2002
DOI: 10.1097/00004728-200205000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Involvement in Mixed Connective Tissue Disease: Comparison With Other Collagen Vascular Diseases Using High Resolution CT

Abstract: CT findings in MCTD were a combination of those in other CTDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…ILD is estimated to occur in up to 65% of patients with MCTD [95]; its major histopathological pattern is that of NSIP, as suggested by histological and radiological data [12,22,96]. It typically manifests within the first 2-4 yrs following disease onset, when other systemic manifestations of SLE, SSc or PM are also present as the disease progresses [93,95].…”
Section: Mixed Ctdmentioning
confidence: 99%
See 2 more Smart Citations
“…ILD is estimated to occur in up to 65% of patients with MCTD [95]; its major histopathological pattern is that of NSIP, as suggested by histological and radiological data [12,22,96]. It typically manifests within the first 2-4 yrs following disease onset, when other systemic manifestations of SLE, SSc or PM are also present as the disease progresses [93,95].…”
Section: Mixed Ctdmentioning
confidence: 99%
“…It typically manifests within the first 2-4 yrs following disease onset, when other systemic manifestations of SLE, SSc or PM are also present as the disease progresses [93,95]. Rarely, the ILD-related symptoms may be the predominant or first manifestation of the disease [96]. In a group of 35 patients with MCTD and ILD undergoing thoracic imaging, SAITO et al [96] reported three patients with only respiratory problems, who were initially believed to have IPF but later diagnosed with MCTD.…”
Section: Mixed Ctdmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients at risk of developing progressive pulmonary fibrosis are currently identified by the presence of lung inflammation. Lung inflammation is usually demonstrated by an increase in neutrophils or eosinophils on differential cell counts of bronchoalveolar lavage (BAL) fluid (4,5) or by radiographic techniques (6,7). Stratification of patients into risk groups according to the presence of lung inflammation is imprecise; some patients with normal findings on BAL fluid differential cell count experience progressive pulmonary fibrosis, whereas some patients with lung inflammation have stable lung function for several years (4).…”
Section: Group 1 Suggested the Possibility That These T Cells Might Imentioning
confidence: 99%
“…Symmetrical ground glass opacity predominantly in the lower lung segments, as in nonspecific interstitial pneumonitis, compatible with the diagnosis of MCTD, was demonstrated ( fig. 1) [10,11].…”
Section: Case Reportmentioning
confidence: 99%